2015
DOI: 10.1155/2015/942928
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Physical Quality of Locally Packaged Drinking Water in Kampala, Uganda

Abstract: Objective. To assess the bacteriological and physical quality of locally packaged drinking water sold for public consumption. Methods. This was cross-sectional study where a total of 60 samples of bottled water from 10 brands and 30 samples of sachet water from 15 brands purchased randomly were analyzed for bacteriological contamination (total coliform and faecal coliform per 100 mL) using membrane filtrate method and reported in terms of cfu/100 mL. Results. Both bottled water and sachet water were not contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
5
14
0
Order By: Relevance
“…The results of this study found that factoryproduced sachet water in Bo is generally safe but that the quality of hand-tied water sachets is inconsistent. This conclusion was also reached by similar studies in Ghana (Oyelude and Ahenkorah, 2012) and Uganda (Halage et al, 2015), and was the conclusion of a systematic review of the global literature (Williams, 2015) on commercial drinking water safety. The hand-tying process introduces the risk of faecal and non-faecal coliform contamination from water workers (Oludairo, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…The results of this study found that factoryproduced sachet water in Bo is generally safe but that the quality of hand-tied water sachets is inconsistent. This conclusion was also reached by similar studies in Ghana (Oyelude and Ahenkorah, 2012) and Uganda (Halage et al, 2015), and was the conclusion of a systematic review of the global literature (Williams, 2015) on commercial drinking water safety. The hand-tying process introduces the risk of faecal and non-faecal coliform contamination from water workers (Oludairo, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…Overall, the different sources of drinking water sampled in this study revealed more healthy water sources than those reported by [31] [45] and even in neighbouring Kampala, Uganda [46], an indication that the sampled sachet water in this study is safer for drinking and adequate for domestic water purposes.…”
Section: B Physicochemical Parameterssupporting
confidence: 43%
“…Before water can be described as potable, it has to comply with certain physical, chemical and microbiological standards which are designed to ensure that the water is potable, safe for drinking thus studies have been conducted to ascertain these parameters in varying drinking water sources [27][28][29][30][31][32], well water [33][34][35][36][37], borehole water [38][39][40][41][42][43], lake [44], packaged water [45][46] and stream/river water [47][48]. It on these bases that this research is conducted to determine the qualities of drinking water sources in Idu district, Abuja, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Halega et al found World Journal of Pharmacy and Pharmaceutical Sciences stakeholders to intensify surveillance activities and enforce strict hygienic measures to packaged water industries and retail outlets to improve water quality (Halega, 2015). Out of the twelve water samples analysed in the current study, only samples B, D, E and G could be considered for recommendation, having satisfied all the parameters tested (table 9).…”
Section: Discussionmentioning
confidence: 90%